Green Marketing That Influence Customer Purchase Decision Based On Their Behavior And Attitude - Yanto Ramli; Daru Asih; Mochamad Soelton (Jurnal Doktor Manajemen (JDM), 2020)
Indonesia has been taking serious attention concerning the disposal of plastic waste in the ocean. Terrible data concerning plastic trash in the Ocean, harm and kill lots of animals around the ocean where plastic waste was found in the stomach of the sea animals. The purpose of this study is to analyze and implement green marketing in the fast food restaurants to promote and educate customers about the dangers of using plastic products and reduce them from the fast food restaurants. The research is to analyze the customer behavior and attitude towards their purchase decision in relating to green marketing as the intervening variable. The data collection is done through distribution of questionnaire, where the population is consisted of customers from KFC restaurants in Jakarta, Indonesia. This is a descriptive and verification research, the descriptive methods is based on assessment analysis and the verification methods is based on quantitative analysis. The sample determination is done through Simple Random Sampling and the analysis technique is using Partial Least Square (PLS). The results show that customer behavior and customer attitude have positive and significant effect towards green marketing and customer behavior has the most significant influence towards green marketing compared to customer attitude. The results show that the KFC customers' awareness concerning the plastic waste is still low eventhough they understand the danger of the plastic waste, but gradually based on their behavior it start to increase after implementing green marketing and to educate them the danger of plastic waste and the limitation of plastic products in the restaurants.